A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge Regarding Prevention of Anemia among Adolescent Girls in A Selected Senior Secondary Schools of, Bharatpur - Gopal, Ram; Chand, Tara (International Journal of Social Sciences and Management, 2017)
Anemia is a condition in which the number of red blood cells or the amount of hemoglobin is low. Red blood cells contain hemoglobin protein that it enables them to carry oxygen from the lungs and deliver it to all parts of the body. A study conducted to assess the effectiveness of structured teaching programme on knowledge regarding prevention of anemia among adolescent girls in a selected senior secondary schools of Bharatpur. During the study, 60 adolescence girls were selected for them pretest is administered for assessing knowledge. After evaluation pretest score was showing lower knowledge regarding prevention of anemia then structured teaching program on knowledge of prevention from anemia administered after one week post test conducted by using same questionnaire this time girls shows increased knowledge regarding prevention of anemia and they are following healthy food habits for the prevention of anemia. Results showing adequate knowledge various methods are used for measuring the variables such as mean, mode, and standard deviation for significance of demographic variables chi square test were used there is no significant demographic variables. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 192-197